Long-term In Vivo Calcium Imaging of Astrocytes Reveals Distinct Cellular Compartment Responses to Sensory Stimulation. (26th November 2016) - Stobart, Jillian L; Ferrari, Kim David; Barrett, Matthew J P; Stobart, Michael J; Looser, Zoe J; Saab, Aiman S; Weber, Bruno
Abstract: Localized, heterogeneous calcium transients occur throughout astrocytes, but the characteristics and long-term stability of these signals, particularly in response to sensory stimulation, remain unknown. Here, we used a genetically encoded calcium indicator and an activity-based image analysis scheme to monitor astrocyte calcium activity in vivo. We found that different subcellular compartments (processes, somata, and endfeet) displayed distinct signaling characteristics. Closer examination of individual signals showed that sensory stimulation elevated the number of specific types of calcium peaks within astrocyte processes and somata, in a cortical layer-dependent manner, and that the signals became more synchronous upon sensory stimulation. Although mice genetically lacking astrocytic IP3R-dependent calcium signaling ( Ip3r2 −/− ) had fewer signal peaks, the response to sensory stimulation was sustained, suggesting other calcium pathways are also involved. Long-term imaging of astrocyte populations revealed that all compartments reliably responded to stimulation over several months, but that the location of the response within processes may vary. These previously unknown characteristics of subcellular astrocyte calcium signals provide new insights into how astrocytes may encode local neuronal circuit activity.